Studi Karakteristik Biogas dari Kotoran Sapi dengan Penambahan Jerami - La Ode Ahmad Barata; Jenny Delly; Samhuddin (Piston: Jurnal Teknologi, 2024)
Cow dung is one of the abundant energy resources, especially in rural areas, which has the potential to become an option in reducing people's dependence on fuel oil. This study aims to analyse the characteristics of biogas from cow dung as an alternative energy. The effect of paddy straw on the biogas production rate and flame characteristics was also analysed. The parameters studied were temperature, pressure, and detected gas on biogas production and flame characteristics. The results showed that biogas from cow dung produced a light blue biogas flame, with a pungent odour at a retention time period of 14 days. Flame characteristics with blue colour were observed on the 21st day of retention time, and the pungent odour (considered as a sulphur, and a carbon monoxide) was relatively reduced. Combustible gases were identified by the gas detector as EX; 100%. Other elements such as sulphur and carbon monoxide were indicated as H2S and CO by the gas detector. The intensity of these two elements decreased as the retention time increased up to 28 days. The addition of the straw of 10% of the cow dung increased the pressure rate and mass of biogas produced on day 7. The biogas combustion test on day 14 showed that the addition of straw reduced the intensity of methane gas, which was characterized by a pale blue flame due to the dominance of carbon monoxide. The effect of straw addition on biogas intensity was observed on day 21, in which the visual intensity of the flame was greater than the feedstock without the straw. In the retention time above 21 days, the straw biomass has been completely degraded, thus increasing the intensity of the burning gas flame. This study recommends carefully handling of straw biomass for additional feedstock and catalyst in the biogas production of cow solid manure such as shredding, ideal composition, and pre-treatment of non-degradable substances.